2017
DOI: 10.1371/journal.pone.0171676
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between RASSF1A gene promoter methylation and the susceptibility and prognosis of melanoma: A meta-analysis and bioinformatics

Abstract: BackgroundThe function of the tumor suppressor gene RASSF1A in cancer cells has been detailed in many studies. However, due to the methylation of its promoter, the expression of RASSF1A is missing in most cancers. In the literature, we found that the conclusion regarding the relationship between RASSF1A gene promoter methylation and the susceptibility and prognosis of melanoma was not unified. This study adopts the use of a meta-analysis and bioinformatics to explore the relationship between RASSF1A gene promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
0
16
2
Order By: Relevance
“…Conversely, our data did not demonstrate any correlation of RASSF1 with survival. In this regard, previous reports have identified RASSF1 as an independent prognostic factor; however, in a recent meta‐analysis no significant association with survival was found . Although Kaplan–Meier and univariate Cox regression analyses indicated that methylation correlated with poor prognosis, in our cohort only Breslow index and ulceration were independent predictors of patient survival.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Conversely, our data did not demonstrate any correlation of RASSF1 with survival. In this regard, previous reports have identified RASSF1 as an independent prognostic factor; however, in a recent meta‐analysis no significant association with survival was found . Although Kaplan–Meier and univariate Cox regression analyses indicated that methylation correlated with poor prognosis, in our cohort only Breslow index and ulceration were independent predictors of patient survival.…”
Section: Discussioncontrasting
confidence: 83%
“…In this regard, previous reports have identified RASSF1 as an independent prognostic factor; 13 however, in a recent meta-analysis no significant association with survival was found. 28 Although Kaplan-Meier and univariate Cox regression analyses indicated that methylation correlated with poor prognosis, in our cohort only Breslow index and ulceration were independent predictors of patient survival. Both histopathological features are wellknown prognostic factors; therefore, methylation events may have clinical utility providing additional prognostic information to these conventional parameters in routine practice.…”
Section: Discussioncontrasting
confidence: 57%
“…Several meta-analysis studies showed an association between RASSF1A promoter hypermethylation and different types of tumors as well as biomarker value of the RASSF1A methylation status (47)(48)(49). This study represents the first meta-analysis of published studies to evaluate the association of RASSF1A promoter hypermethylation with testicular cancer.…”
Section: Discussionmentioning
confidence: 84%
“…A number of meta-analysis studies have shown that there is a correlation between hyper-methylation of RASSF1A promoter and different types of tumors, as well as the value of biomarkers for the methylation status of RASSF1A [21][22][23][24][25] . In addition, an important implication from our findings is that hyper-methylation of the promoter of tumor suppressor loci in normal breast tissue may be a precursor to local recurrence.…”
Section: Discussionmentioning
confidence: 99%